Presença de propósito de vida em idosos avaliados pelo estudo SAPPA – na pandemia COVID-19 - Soares, Iasmin Machado (Brasil, 2022)
BACKGROUND: The relationship between the presence of purpose in life in the elderly in the SAPPA study, present in the municipality of Coari during the pandemic, was evaluated. METHODS: Data collected through a consultation in the registry of the UBS, of the homes of elderly people aged 65 years and over with diabetes. To assess the presence of purpose in life, those selected were submitted to a semi-structured questionnaire. For the descriptive and statistical analysis of the data, the program IBM/Stata MB, version 14.0 was used. RESULTS: The elderly interviewed have the presence of a purpose in life with a confidence interval of 95.5%, in the analysis of associated statistics, there was no significant difference between men and women, in relation to age, income and time of study, disassembling there was no difference in the life purpose. CONCLUSION: The presence of purpose in life in the elderly interviewed and even if they present differences in social profile, age, sex, income, and time of study, does not change the presence of purpose in life.